FRI0255 Patterns of disease activity impact on organ damage in systemic lupus erythematosus. (15th June 2017) - Bortoluzzi, A; Padovan, M; Silvagni, E; Scirè, CA; Govoni, M
Abstract : Background: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease characterized by fluctuating disease activity in which adverse long-term outcomes remain a major challenge. In the face of extreme individual unpredictability of the disease course over time, four different patterns can be defined, as elsewhere described [1], using SLEDAI-2K (Systemic Lupus Erythematosus Disease Activity Index-2K) excluding serology in order to focus on clinical activity. The patterns are clinical quiescent disease (CQD), chronic active disease (CAD), relapsing-remitting disease (RRD) and minimal disease activity (MDA). Objectives: The aim of our study was to assess the association between different disease activity patterns and damage accrual in SLE patients. Methods: Patients with SLE registered at our Lupus Clinic at the Rheumatology Unit, between 1 January 2013 and 1 October 2016, were included. Demographic and clinical variables included age, gender, age at SLE onset, major organ involvement. SDI (Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) Damage Index) was categorized as absent (SDI=0) or present (SDI ≥1), Disease activity patterns (CQD, MDA, RRD, CAD) were retrospectively assessed. Drugs used in the treatment of SLE, including hydroxychloroquine, cumulative dose of glucocorticoid (prednisone equivalent >10 g) and other immunosuppressive drugs, were also collected. Multivariate logistic regression analyses were performed to identify disease patterns associated with damage accrual. Results are presented as odds ratio (OR) and 95% confidence intervals (CI). Results: A total of 473 Caucasian patients were observed, mainly female (89.4% F, 10.6% M), mean age 52.6 years (± 14.9 SD). In our cohort, the disease activity pattern distribution was as follows: 65.4% CQD (290 pts), 21.5% RRD (91 pts), 6.1% MDA (28 pts) and CAD in 19.1% of the cases (64 pts). Damage was significantly more frequent in CAD subset (81.2%, 52/64 pts) versus 54.5% in CQD (158/290 pts), 50% in MDA (14/28 pts) and 58.2% in RRD (53/91 pts). Compared to a CQD course, CAD pattern was independently associated with overall damage after controlling for factors including gender, disease duration, cumulative glucocorticoid dosage, major individual organ involvement (neuropsychiatric and renal), positive antiphospholipid antibody profile, exposures to cyclophosphamide and hydroxychloroquine (Table 1 ). Conclusions: Our results demonstrated that a clinically and persistent CAD triples the risk of damage compared to milder or relapsing courses, while hydroxychloroquine appeared to have a "protective" effect. Identifying the prevailing pattern of disease activity in every patient can be translated into a more effective personalized preventing strategy to reduce damage accrual and improve outcomes. References: M. Zen et al. Disease activity patterns in a monocentric cohort of SLE patients: a seven-year follow-up study, Clin. Exp. Rheumatol. 30 (2012) 856–863. Disclosure of Interest: None declared